Domestic airborne fine particulate matter exposure and asthma control among children receiving inhaled steroid treatment. Issue 3 (May 2014) - Woods, K. E.; Apsley, A.; Semple, S.; Turner, S. W.
The aims of the present study were to measure domestic PM2.5 exposure and explore relationships with indices of asthma severity and control in children prescribed inhaled corticosteroids (ICSs). Disease severity was determined by questionnaire and spirometry. Asthma control was assessed by 5-day peak flow variability (PFV) and children's asthma control test (CACT) on the 1st and 5th day of peak flow testing. Concentrations of PM2.5 were measured over a 24-h period. Twenty-two children were recruited, mean age 11.0 years. Across the 22 homes the median time weighted average (TWA) PM2.5 concentration (range) was 7.4 μg/m 3 (2.0–150.0) and was significantly higher in the seven homes where smoking was reported (24.0 μg/m 3 ) than non-smoking homes (6.0 μg/m 3 ), p=0.001. There was a positive association between TWA PM2.5 and PFV (rho = 0.55, p = 0.015, n = 19) and a negative association between TWA PM2.5 and CACT (rho = − 0.56, p = 0.010, n = 20). TWA PM2.5 exposure was not related to indices of asthma severity. Peak PM2.5 concentration was not associated with any outcome. This exploratory study suggests that even at relatively low concentrations, there is an exposure–response relationship between increasing indoor air PM2.5 concentrations and poorer asthma control in children prescribed ICSs.